Hyperautomation Use Cases (Case Studies) - Parakala, Adityamallikarjunkumar (International Journal of AI, BigData, Computational and Management Studies, 2023)
Hyperautomation, often seen as the next step in digital transformation, is the combination of Robotic Process Automation (RPA), Artificial Intelligence (AI), Machine Learning (ML), process mining & advanced analytics to create intelligent, adaptable & scalable automation ecosystems. Hyperautomation is different from regular automation since it can coordinate whole end-to-end business processes instead of just more repetitive, rule-based tasks. This makes businesses more efficient, helps them make decisions based on their information, and makes them more resilient. Actual world case studies show the actual importance of this change. For example, companies in banking, healthcare, manufacturing & government have all seen measurable benefits, such as lower expenses, faster process efficiency, better compliance with rules & happier customers. These examples not only show how revolutionary hyperautomation can be, but they also show how more and more businesses are adopting it as they try to use the latest technologies in their work. These case studies show how hyperautomation may help businesses keep up with quickly changing market requirements while also maintaining their operational excellence. As businesses do more and more online, hyperautomation is becoming more than just a way to make processes more efficient; it is becoming a key part of innovation, flexibility & long-term growth. This essay looks at a lot of different use examples to show that hyperautomation is not only the latest technology; it is also a strategic tool that will change how businesses work in the future